The combination of SMRT sequencing and Illumina sequencing highlights organ-specific and age-specific expression patterns of miRNAs in Sika Deer - Jia, Boyin; Wang, Xue; Ma, Fuquan; Li, Xin; Han, Xintong; Zhang, Linlin; Li, Jianming; Diao, Naichao; Shi, Kun; Ge, Chenxia; Yang, Fuhe; Du, Rui (Frontiers in Veterinary Science, 2022)
Due to the lack of high-quality Sika Deer (Cervus nippon) transcriptome and sRNAome across multiple organs or development stages, it is impossible to comprehensively analyze the mRNA and miRNA regulatory networks related to growth, development and immunity response. In this study, we firstly used single molecule-real time sequencing (SMRT-seq) and RNA-Sequencing (RNA-Seq) methods to generate transcriptome from ten tissues and four age groups of Sika Deer to help us understand the life cycle and molecular characteristics. A total of 240,846 consensus transcripts were generated with an average length of 2,784 bp. Meanwhile, 4,329 Transcription factors (TFs), 109,000 Simple Sequence Repeats (SSRs) and 18,987 Long non-coding RNAs (LncRNAs) were identified. Secondly, we investigated the global miRNA expression profile across four developmental stages in ten tissues using small RNA sequencing (sRNA-seq). In total, 306 known miRNAs and 143 novel miRNAs were obtained. A large number of miRNAs showed organ-specific and age-specific differential expression patterns. In particular, we found that the organ-specific miRNAs were enriched in the brain, some of which shared only between the brain and adrenal. These miRNAs were involved in maintaining specific functions within the brain and adrenal. Finally, we constructed miRNA–mRNA interaction networks associated with Sika Deer immunity. The results indicated that miRNAs (miR-148a, miR-26a, miR-214, let-7b, etc.) and mRNAs (CD6, TRIM38, C3, CD163, etc.) might play an important role in the immune response of Sika Deer spleen. Together, our study generated an improved transcript annotation for Sika Deer by SMRT-seq and revealed the role of miRNA in regulating the growth, development and immunity response of Sika Deer.